THE STUDY OF ASSOCIATION OF TYPE 2 DIABETES MELLITUS AND TINEA PEDIS : A SYSTEMATIC REVIEW - Novitafalen; Christika, Nathania; Henyta; Azhari, Ririn; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: A common fungal infection that is more common in those with weakened immune systems is tinea pedis. people with diabetes continue to be more prone to tinea pedis than other people because of their compromised vascular and immune systems. Aims : This systematic review is to review the association of type 2 diabetes mellitus and cases of tinea pedis. Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 68 articles, whereas the results of our search on SCIENCE DIRECT brought up 885articles, our search on SAGEPUB brought up 65 articles. The results of the search conducted for the last year of 2014 yielded a total 24 articles for PubMed, 316 articles for SCIENCE DIRECT and 18 articles for SAGEPUB. In the end, we compiled a total of 8 papers, 6 of which came from PubMed, 1 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included eight research that met the criteria. Conclusion: In summary, there are association between the cases of tinea pedis in patients with diabetes mellitus.